ANALISIS KUALITAS AIR MINUM DALAM KEMASAN (AMDK) DI YOGYAKARTA DITINJAU DARI PARAMETER FISIKA DAN KIMIA AIR - Aryani, Titin (Universitas Jenderal Achmad Yani Yogyakarta, 2017)
Backgroud: Nowadays, bottled water has become the most substitute water for cooking drinking water. Although bottled water seemed attractive, it is crucial to assess its quality. Objective: This quantitative study aimed to determine the quality of the 5 brands of bottled water circulating in Yogyakarta, in terms of physical parameters (temperature, smell, taste, color, turbidity, and TDS electroconductivity) and chemical parameters of water (pH, the presence of Cl-ions, and the presence of metals such as Cr, Fe, Zn, Cd). Methods: The sampling technique used was purposive sampling. The instrument used to determine the quality of bottled water is the standard of drinking water quality standards. Result: The results showed that five samples of bottled water circulating in Yogyakarta, are all qualified bottled water both in terms of physical parameters (temperature, smell, taste, color, turbidity, electroconductivity, and TDS) and chemical parameters of water (pH , the presence of Cl-ions, and the presence of metals such as Cr, Fe, Zn, Cd). Conclusion: Five samples of bottled water circulating in Yogyakarta were suitable for consumption. Keywords: Bottled water, water analysis, water quality, water chemistry parameters